Ibnu ZaydÅ«n wa TaqÄlÄ«d Asy-Syiâ€™ri Al-AndalusÄ« - Haque, Arina; Maimunah, Iffat; Wargadinata, Wildana (Departemen Pendidikan Bahasa Arab, 2021)
Andalusian literature is still a great legacy of Islamic civilization in modern times. The discussion of Andalusian literature is still an exciting topic in the Arab literary scene in the modern era. There are many great legacies of Arabic literature that have not been widely studied by academics in Indonesia, especially Arabic literature reviewers. One of the Andalusian literary figures is Ibn Zaidun. Even the fame of Ibn Zaidun in Andaluasi to get the nickname Buhtury from the West. This paper tries to review Andalusian Arabic literature in general and, in particular, the literary tradition of Ibn Zaidun with the background of Andalusian civilization. Using a literature review approach, this paper explains the socio-cultural background of Ibn Zaidun in building a tradition of Arabic literature in the West (Andalusia). This paper shows the significant role of Ibn Zaidun in building an Arabic literary tradition with a local Andalusian style. This literary tradition is even recognized as having a literary quality that is not inferior to Arabic literature in Arab civilization.